Dimensi E-Servqual dan Dampaknya Terhadap E-Satisfaction Layanan Mobile Banking - Nurrahmi Hayani; Saipul Alsukri (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the effect of e-servqual on e-satisfaction on mobile banking customers. The population in this study was all customers of BRI Syariah at State Islamic University sultan Syarif Kasim. The sampling method in this study uses non probability sampling with a purposive sampling technique where this technique takes samples with certain considerations. The data used are primary data and secondary data. Data analysis method used is multiple linear regression methods. The results showed the facts of the six e-servqual variables offered in this study, only the fulfillment, privacy, and responsiveness variables have a significant relationship. While the 3 other variables namely efficiency, reliability and contact do not have a significant influence on e-satisfaction customers of BRI Syariah mobile banking in UIN Suska Riau. These six e-servqual variables have an effect of 62.7% on the e-satisfaction variable while the remaining 37% are approved by other variables not included in this study.